EVALUATION OF SOCIAL RESILIENCE INDEX ON VILLAGE INFRASTRUCTURE, COMMUNITY EMPOWERMENT, AND PUBLIC SERVICE QUALITY (CASE STUDY OF THE 1 BILLION 1 VILLAGE PROGRAM) - Andi Irfan Saputra; Suhardi M Anwar; Hadi Pajarianto; Ilham Tahier, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study evaluates the impact of village infrastructure, community empowerment, and the quality of public services on the achievement of the Developing Village Index (IDM) in Kalaena Kiri Village, East Luwu Regency, in the context of the "1 Billion 1 Village" Program. This study uses a quantitative method with the Structural Equation Modeling (SEM) approach to analyze the relationship between variables. The results of the study show that village infrastructure and the quality of public services have a positive and significant influence on the success of this program, which further has an impact on increasing IDM. In contrast, community empowerment did not show a significant influence on the program or IDM, indicating the need for reformulation in the empowerment strategy. The implications of this study emphasize the importance of infrastructure development and improving the quality of public services as the main factors in the success of village development programs. A holistic approach that integrates various aspects of development is needed to achieve more optimal results in improving village welfare and development.